Effect of pH, ionic strength, and temperature on the phosphate adsorption onto lanthanum-doped activated carbon fiber - Liu, Jianyong; Wan, Lihua; Zhang, Ling; Zhou, Qi (Journal of colloid and interface science, 2011)
The phosphate adsorption onto ACF-La was strongly dependent on pH value and the main mechanism involved in adsorption process varied with the change of solution pH. Moreover, high temperature was in favor of the adsorption process. The background electrolyte (NaCl) not only reduced the uptake amount but also increased the effect of intraparticle diffusion on adsorption of phosphate onto ACF-La. [Display omitted] ► The feasibility of phosphate removal using ACF-La as an adsorbent was investigated. ► The effect of pH on the phosphate adsorption mechanism was identified. ► The effect of ionic strength on the mass transport of phosphate ions onto the ACF-La was examined. ► The behavior of adsorption process by means of evaluating activation energy and thermodynamic parameters was studied. Phosphate removal from polluted water is crucial to preventing eutrophication. Herein, we present the investigation on phosphate adsorption in aqueous solutions by using lanthanum-doped activated carbon fiber (ACF-La). Various batch sorption conditions, e.g., pH, ionic strength, and temperature were tested, and the adsorption mechanisms were discussed. The sorption capacity of ACF-La was higher in acidic solutions than that in basic ones, suggesting that the Lewis acid–base interaction gradually dominated the adsorption process with the increase in pH values. The degree of phosphate removal decreased with the enhancement of the ionic strength of the solution, meaning that the adsorption of phosphate on ACF-La was strongly dependent on ionic strength. Employing the pseudo first- and second-order, and intra-particle diffusion models to evaluate the adsorption kinetics of phosphate onto ACF-La indicated that the second-order model best fits the experimental data. The presence of chloride ion in solutions increased the effect of intra-particle diffusion on the adsorption of phosphate onto ACF-La but reduced the overall rate of the adsorption. The thermodynamic parameters were determined which revealed the feasibility, spontaneity, and endothermic nature of adsorption.